Left atrial volume index in patients with heart failure and severely impaired left ventricular systolic function: the role of established echocardiographic parameters, circulating cystatin C and galectin-3. (November 2017) - Zivlas, Christos; Triposkiadis, Filippos; Psarras, Stelios; Giamouzis, Gregory; Skoularigis, Ioannis; Chryssanthopoulos, Stavros; Kapelouzou, Alkistis; Ramcharitar, Steve; Barnes, Edward; Papasteriadis, Evangelos; Cokkinos, Dennis
Backround: Left atrial (LA) enlargement plays an important role in the development of heart failure (HF) and is a robust prognostic factor. Fibrotic processes have also been advocated to evoke HF through finite signalling proteins. Methods: We examined the association of two such proteins, cystatin C (CysC) and galectin-3 (Gal-3), and other clinical, echocardiographic and biochemical parameters with LA volume index (LAVi) in patients with HF with severely impaired left ventricular ejection fraction (LVEF). Severe renal, liver, autoimmune disease and cancer were exclusion criteria. Results: A total of 40 patients with HF (31 men, age 66.6 ± 1.7) with LVEF = 25.4 ± 0.9% were divided into two groups according to the mean LAVi (51.03 ± 2.9 ml/m 2 ) calculated by two-dimensional transthoracic echocardiography. Greater LAVi was positively associated with LV end-diastolic volume ( p = 0.017), LV end-systolic volume ( p = 0.025), mitral regurgitant volume (MRV) ( p = 0.001), right ventricular systolic pressure (RVSP) ( p < 0.001), restrictive diastolic filling pattern ( p = 0.003) and atrial fibrillation ( p = 0.005). Plasma CysC was positively correlated with LAVi ( R 2 = 0.135, p = 0.019) and log-transformed plasma Gal-3 ( R 2 = 0.109, p = 0.042) by simple linear regression analysis. Stepwise multiple linear regression analysis showed that only MRV ( t = 2.236, p = 0.032), CysC ( t = 2.467, p = 0.019) and RVSP ( t = 2.155, p = 0.038) were significant predictors of LAVi. Conclusions: Apart from known determinants of LAVi, circulating CysC and Gal-3 were associated with greater LA dilatation in patients with HF with reduced LVEF. Interestingly, the correlation between these two fibrotic proteins was positive.